2006
DOI: 10.1162/pres.15.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological Responses to a Social Situation in an Immersive Virtual Environment

Abstract: An experiment was conducted in a Cave-like environment to explore the relationship between physiological responses and each of breaks in presence, and utterances by virtual characters towards the participants. Twenty people explored a virtual environment (VE) that depicted a virtual bar scenario. The experiment was divided into a training and an experimental phase.During the experimental phase breaks in presence (BIPs) in form of whiteouts of the VE scenario were induced for 2 seconds at four equally spaced ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 25 publications
5
116
0
7
Order By: Relevance
“…En el estudio 12 -tabla 1- (Slater et al, 2006), el participante era inmerso en una escena virtual que consistía en un bar con un barman y dos parejas virtuales. Estos avatares (2 mujeres y 2 hombres) daban la impresión de tener consciencia de la presencia del sujeto y frecuentemente dirigían su mirada hacia él.…”
Section: Análisis Descriptivo De Los Estudiosunclassified
“…En el estudio 12 -tabla 1- (Slater et al, 2006), el participante era inmerso en una escena virtual que consistía en un bar con un barman y dos parejas virtuales. Estos avatares (2 mujeres y 2 hombres) daban la impresión de tener consciencia de la presencia del sujeto y frecuentemente dirigían su mirada hacia él.…”
Section: Análisis Descriptivo De Los Estudiosunclassified
“…In the pursuit to trigger emotions in a more or less controlled manner, a range of methods have been applied: actors, images (IAPS), sounds (e.g., music), (fragments of) movies (Westerink et al, 2008b), speech (Van den Broek, 2004), commercials (Hazlett andHazlett, 1999;Poels and Dewitte, 2006), games, agents / serious gaming / virtual reality (Slater et al, 2006;Westerink et al, 2008a), reliving of emotions ( Van den Broek, 2004), and real world experiences (Healey and Picard, 2005); see also Box 1. However, how to know which of these methods actually triggered participants' true emotions?…”
Section: Validitymentioning
confidence: 99%
“…Hence, we advise to record three affective signals, or have at least three features derived from them, for each construct under investigation, in well controlled research. Moreover, qualitative and subjective measures should accompany the signals (e.g., questionnaires, video recordings, interviews, and Likert scales); e.g., see (Hazlett and Hazlett, 1999;Healey and Picard, 2005;Slater et al, 2006;Van den Broek, 2004;Westerink et al, 2008a). Please consult also Section 3.1 on this topic.…”
Section: Triangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A visual cliff type of environment has been used where participants were in an IVE that shows a precipice, and their heart rate increased significantly [13][14][15]. Both skin conductance, heart rate and heart rate variability have been shown to respond significantly in the context of general social situations [16], and social situations that are highly stressful [17]. It has also been found that there are similarities in behavior when participants play handball in virtual reality compared to physical reality [18].…”
Section: Introductionmentioning
confidence: 99%